Solve for \( y \). \[ \frac{1}{y-4}+\frac{2}{y+3}=\frac{10}{y^{2}-y-12} \] If there is more than one solution, separate them with commas. If there is no solution, dick on "No solution". \( y=\square \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve for \( y \), we first notice that the denominator on the right side, \( y^2 - y - 12 \), can be factored as \( (y-4)(y+3) \). We start with the equation: \[ \frac{1}{y-4} + \frac{2}{y+3} = \frac{10}{(y-4)(y+3)} \] Next, we can multiply each term by \( (y-4)(y+3) \) to eliminate the fractions: \[ (y+3) + 2(y-4) = 10 \] Simplifying the left-hand side gives: \[ y + 3 + 2y - 8 = 10 \] \[ 3y - 5 = 10 \] \[ 3y = 15 \] \[ y = 5 \] Now, we should check if this solution does not make any denominator zero: - \( y - 4 = 5 - 4 = 1 \) (not zero) - \( y + 3 = 5 + 3 = 8 \) (not zero) The solution \( y = 5 \) is valid. Therefore, the final answer is: \( y = 5 \)